2014
DOI: 10.1002/acn3.33
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pupillary light reflex with chromatic pupillometry in G aucher disease

Abstract: The hallmark of neuronopathic Gaucher disease (GD) is oculomotor abnormalities, but ophthalmological assessment is difficult in uncooperative patients. Chromatic pupillometry is a quantitative method to assess the pupillary light reflex (PLR) with minimal patient cooperation. Thus, we investigated whether chromatic pupillometry could be useful for neurological evaluations in GD. In our neuronopathic GD patients, red light-induced PLR was markedly impaired, whereas blue light-induced PLR was relatively spared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Chaperones can cross the blood-brain barrier and selectively bind to misfolded glucocerebrosidases facilitating the correction of protein misfolding and improving enzyme function. A recent pilot study investigating the efficacy of PCT in patients with Type III GD reported marked improvements in saccadic initiation latency and pupillary light reflex dysfunction107 using chromatic pupillometry device 108. Future studies should evaluate the efficacy of PCT in treating ophthalmic manifestations of GD.…”
Section: Discussionmentioning
confidence: 99%
“…Chaperones can cross the blood-brain barrier and selectively bind to misfolded glucocerebrosidases facilitating the correction of protein misfolding and improving enzyme function. A recent pilot study investigating the efficacy of PCT in patients with Type III GD reported marked improvements in saccadic initiation latency and pupillary light reflex dysfunction107 using chromatic pupillometry device 108. Future studies should evaluate the efficacy of PCT in treating ophthalmic manifestations of GD.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the myoclonus scores with action, functional tests, and stimulus sensitivity were evaluated in patients who could follow the instructions. PLR was assessed in all patients using an infrared pupillometer, as reported in an earlier study . In this study, we selected a 1‐s red stimulus of 270 cd/m 2 and evaluated the mean values of the initial constriction rate and latency.…”
Section: Methodsmentioning
confidence: 99%
“…In the experiment, a long wavelength (635 ± 5 nm) red light and a short wavelength (470 ± 7 nm) blue light were used at two different light intensities (10 and 100 cd/ m 2 ). The light stimulation conditions were adjusted in accordance with the method of Kawasaki and Kardon [ 10 ],[ 12 ] while the measurement validity was also confirmed [ 30 ],[ 31 ]. PLRs for light stimuli were simply recorded as single trial measure.…”
Section: Methodsmentioning
confidence: 99%